Seaberry extract with ursolic acid improves anxiety about urinary dysfunction in Japanese adults - Takara, Tsuyoshi; Yamamoto, Kazuo; Suzuki, Naoko; Shimoda, Hiroshi (Functional foods in health and disease, 2017)
Background: The seaberry is a yellow berry cultivated in China, Northern Europe, and West Asian countries. Numerous biological activities of seaberries have been reported, and we recently found that ursolic acid and a flavonoid in seaberry extract (SBE) suppressed the contraction of bladder muscle specimens and collagen gel containing bladder smooth muscle cells. However, the influence of SBE on urinary problems of Japanese adults has not been investigated. Therefore, we conducted a clinical trial of SBE supplementation in Japanese subjects with mild urinary dysfunction.Methods: We examined the effect of SBE (200 or 400 mg daily) containing ursolic acid (0.18 or 0.36 mg) in a randomized double-blind placebo-controlled study. Capsules containing SBE or placebo were administered for 8 weeks to Japanese men and women with mild urinary dysfunction. After 4 and 8 weeks of treatment, urinary symptoms were evaluated by using the King’s Health Questionnaire (KHQ) and the overactive bladder syndrome score (OABSS).Results: There was significant improvement of the KHQ emotion domain score after intake of 400 mg/day of SBE for 8 weeks compared with placebo. The answers to “Does your bladder problem make you depressed?” and “Does your bladder problem make you feel bad about yourself?” were significantly improved by SBE (400 mg/day) at 8 weeks. In the OABSS, the item “How often do you have a sudden desire to urinate, which is difficult to defer?” was significantly improved by SBE compared with placebo. Laboratory tests did not reveal any abnormalities suggesting adverse effects SBE. Conclusions: Intake of SBE (400 mg/day for 8 weeks) improved several emotional parameters related to urinary dysfunction. SBE may be useful for reducing moderate urinary symptoms.Keywords: King’s health questionnaire; overactive bladder syndrome score; seaberry; ursolic acid; overactive bladder; urination; micturition